Implementasi Manajemen Konflik Pada Siswa Bolos Sekolah Di SMA Negeri 1 Tiris - Ira Fasira; Hamidatuz Zakkiyah Aprilia; Putri Nabila Vidayanti; Ani Qotuz Zuhro’ Fitriana (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This research focuses on the conflict management of students skipping school conducted by counseling teachers. The background of the research is the decline in student academic achievement and the efforts of counseling teachers in handling conflicts of students skipping school so as to get better results. The research was conducted with the aim of knowing the factors, impacts and efforts of counseling teachers in handling conflicts of students skipping school. The research is descriptive qualitative in nature which is used as a theory development that has been built from data obtained in the field or research site. Informants in the study were the counseling teacher and 5 students who often skipped school at SMA Negeri 1 Tiris. Data collection techniques using observation and interviews. The results of the research obtained are that students skip class due to lack of learning motivation, environment, boredom, dislike of teachers and certain subjects. From this skipping behavior, it has an impact such as missing lessons, declining academic achievement to not going to class. The handling efforts made by the BK teacher are by giving points, coaching, calling parents and a stamped statement.